2023
DOI: 10.1002/ange.202300481
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Synthesis of Axially Chiral Diaryl Ethers through Enantioselective Desymmetrization

Abstract: Axially chiral diaryl ethers are a type of unique atropisomers bearing two potential axes, which have potential applications in a variety of research fields. However, the catalytic enantioselective synthesis of these diaryl ether atropisomers is largely underexplored when compared to the catalytic asymmetric synthesis of biaryl or other types of atropisomers. Herein, we report a highly efficient catalytic asymmetric synthesis of diaryl ether atropisomers through an organocatalyzed enantioselective desymmetriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Collectively, both the desymmetric process and the kinetic resolution process play vital roles in the construction of 3aa with excellent enantioselectivity. Based on our control experiments and reported literature, a possible catalytic cycle was proposed as Scheme (3) . First, an active catalyst NHC-cat was formed by the reaction between NHC-1 and Cs 2 CO 3 .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, both the desymmetric process and the kinetic resolution process play vital roles in the construction of 3aa with excellent enantioselectivity. Based on our control experiments and reported literature, a possible catalytic cycle was proposed as Scheme (3) . First, an active catalyst NHC-cat was formed by the reaction between NHC-1 and Cs 2 CO 3 .…”
Section: Results and Discussionmentioning
confidence: 99%
“…In 2008, Clayden’s group documented the first enantioselective synthesis of an atropisomeric diaryl ether through dynamic resolution . Thereafter, the Clayden, Zeng and Zhong, and Yang groups realized the atroposelective construction of the axially diaryl ethers via biocatalytic or organocatalytic desymmetrization of prochiral diaryl ethers respectively (Scheme a) . In 2018, Gustafson and co-workers developed a C­(sp 2 )–H alkylation with nitroalkanes to access enantioenriched diaryl ethers with a quaternary ammonium salt (derived from quinine) as the catalyst .…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, many chemists have made significant strides in developing numerous asymmetric synthesis methods to create a diverse range of atropisomers [151][152][153][154][155][156][157][158][159][160][161][162][163][164][165][166][167][168] and these methodologies are continually evolving. Furthermore, some atropisomers, not covered in this review, such as those C▬B bonded, 168 C▬O bonded, 169 C▬S bonded 170 atropisomers, also been successfully synthesized, albeit without their activities being tested. This expands the structural diversity available and provides additional synthetic insights for the development of future atropisomeric drugs.…”
Section: Medium-sized Ring and Macrocycle Bioactive Atropisomersmentioning
confidence: 99%
“…Diaryl ether, another type of nonbiaryls containing C-O-C bonds, was proved by Mislow et al in 1982 [21], but its synthesis was not reported until 1998 by Kinoshita et al [22]. At present, there is still a large room for research on this kind of compounds, and new progresses have been developed for the synthesis of these compounds by using organocatalytic strategies in recent years [23].…”
Section: Introductionmentioning
confidence: 99%